Loss : the politics of mourning - Eng, David L., 1967-; Kazanjian, David, 1967- (University of California Press, 2003)
Taking stock of a century of pervasive loss--of warfare, disease, and political strife--this eloquent book opens a new view on both the past and the future by considering "what is lost" in terms of "what remains." Such a perspective, these essays suggest, engages and reanimates history